BIOPRODUCTION AND CHARACTERIZATION OF SILVER NANOPARTICLES FROM MICROALGAE ASTERACYS QUADRICELLULARE, ITS ANTIMICROBIAL AND ANTIBIOFILM ACTIVITIES - SMITA.S.KATTARATH,; GEETHA RAMANI.D, (International Journal of Pharma and Bio Sciences, 2017)
Green synthesis of silver nanoparticles (SNPs) using microalgae is an emerging technology. In the present investigation, silver nanoparticles were synthesized using microalga Asteracys quadricellulare.The extract incubated with AgNO3. The formation of nanoparticles characterized by (UV-Vis) spectroscopy. Absorption spectra of Ag nanoparticles had absorbance maxima at 237 - 309nm. (SEM) analysis confirmed AgNPs were spherical within 100nm size, (FTIR) showed bands for cell components like proteins, lipids and carbohydrates and (XRD) data illustrated the crystalline nature of silver nanoparticles that clearly showed the Bragg reflections at 2θ values. Bioreduction of algal extract showed a gradual colour change of extract by formation of silver nanoparticles. The goal of this research was to evaluate the anti-biofilm and antimicrobial activities of silver nanoparticles (AgNPs) against microorganisms of clinical interest. Here, silver nanoparticles showed a strong antimicrobial and antibiofilm effect. This work confirms that microalga A. quadricellulare can be used as a suitable system for SNPs synthesis as an eco-friendly and in a cost effective manner.